Pemberdayaan Siswa SMK Dalam Meningkatkan Kemampuan untuk Persiapan Karir dan Pendidikan di Puncak CBD Apartment - Juliardi, Ferry; Triyoso, Charles; Surya, Alvin; Cristie, Hizkia; Hadi, Ali; Wahyuningtyas, Emmy; Suharso, Akbar Bayu Kresno (PENITI BANGSA (Pemanfaatan Ilmu Pengetahuan dan Teknologi bagi Masyarakat), 2025)
This community service activity aims to enhance the skills and knowledge of Vocational High School (SMK) students in the field of Information Technology. The program also provides learning and practical experience for university students through direct involvement in the empowerment activities for SMK students at the Computer Science Society community, Puncak CBD Apartment No. 8D, Surabaya. The location and characteristics of the community offer significant potential for broadening students’ insights and increasing their knowledge of technological developments. The activity focuses on training participants to create simple web pages using HTML and CSS programming languages. The results indicate an improvement in students’ understanding of HTML and CSS. In addition, participants showed high enthusiasm and were able to apply the material in creating websites. This enthusiasm emerged because their schools had not previously provided instruction in HTML and CSS, making this training a valuable opportunity to gain new and relevant knowledge.